Subsurface biogeochemical cycling of nitrogen in the actively serpentinizing Samail Ophiolite, Oman - Rempfert, Kaitlin R.; Nothaft, Daniel B.; Kraus, Emily A.; Asamoto, Ciara K.; Evans, R. Dave; Spear, John R.; Matter, Juerg M.; Kopf, Sebastian H.; Templeton, Alexis S. (Frontiers in Microbiology, 2023)
Nitrogen (N) is an essential element for life. N compounds such as ammonium (NH4+) may act as electron donors, while nitrate (NO3-) and nitrite (NO2-) may serve as electron acceptors to support energy metabolism. However, little is known regarding the availability and forms of N in subsurface ecosystems, particularly in serpentinite-hosted settings where hydrogen (H2) generated through water–rock reactions promotes habitable conditions for microbial life. Here, we analyzed N and oxygen (O) isotope composition to investigate the source, abundance, and cycling of N species within the Samail Ophiolite of Oman. The dominant dissolved N species was dependent on the fluid type, with Mg2+-HCO3- type fluids comprised mostly of NO3-, and Ca2+-OH− fluids comprised primarily of ammonia (NH3). We infer that fixed N is introduced to the serpentinite aquifer as NO3-. High concentrations of NO3- (>100 μM) with a relict meteoric oxygen isotopic composition (δ18O ~ 22‰, Δ17O ~ 6‰) were observed in shallow aquifer fluids, indicative of NO3- sourced from atmospheric deposition (rainwater NO3-: δ18O of 53.7‰, Δ17O of 16.8‰) mixed with NO3- produced in situ through nitrification (estimated endmember δ18O and Δ17O of ~0‰). Conversely, highly reacted hyperalkaline fluids had high concentrations of NH3 (>100 μM) with little NO3- detectable. We interpret that NH3 in hyperalkaline fluids is a product of NO3- reduction. The proportionality of the O and N isotope fractionation (18ε / 15ε) measured in Samail Ophiolite NO3- was close to unity (18ε / 15ε ~ 1), which is consistent with dissimilatory NO3- reduction with a membrane-bound reductase (NarG); however, abiotic reduction processes may also be occurring. The presence of genes commonly involved in N reduction processes (narG, napA, nrfA) in the metagenomes of biomass sourced from aquifer fluids supports potential biological involvement in the consumption of NO3-. Production of NH4+ as the end-product of NO3- reduction via dissimilatory nitrate reduction to ammonium (DNRA) could retain N in the subsurface and fuel nitrification in the oxygenated near surface. Elevated bioavailable N in all sampled fluids indicates that N is not likely limiting as a nutrient in serpentinites of the Samail Ophiolite.